Governance of Lithium Resources in Puno: Opportunities and Challenges - Ramos Zaga, Fernando Antonio (2023)
Lithium plays an increasingly vital role in our transition towards renewable energy sources and the production of batteries for electric vehicles. The main objective of this article is to analyze the diverse governance regimes of Argentina, Chile and Bolivia within the Lithium Triangle. It also aims to examine the challenges these nations face in achieving their policy objectives. In this way, valuable lessons can be drawn from these experiences that can be applied to the development of the Puno region. To this end, a comprehensive literature review of lithium production, its value chain and the parties involved has been carried out. The results indicate that each country in the Lithium Triangle has followed unique strategies based on different governance structures and regulatory environments. Their policies focus on increasing the efficiency and profitability of lithium production while ensuring state control of the associated benefits. It is concluded that it is important to recognize both the advantages and disadvantages of lithium extraction for sustainable development purposes. Engaging civil society stakeholders along with political bodies at different levels is crucial to discuss the geopolitical implications as well as the environmental concerns surrounding lithium mining operations.